Advances in the Role of Endothelial Cells in Cerebral Small Vessel Disease - Bai, Tao; Yu, Shijia; Feng, Juan (Frontiers in Neurology, 2022)
Cerebral small vessel disease (CSVD) poses a serious socioeconomic burden due to its high prevalence and severe impact on the quality of elderly patients’life. The pathological changes of CSVD mainly influence small cerebral arteries, microarteries, capillaries and small veins, which are usually caused by multiple vascular risk factors. CSVD is often identified on brain magnetic resonance imaging (MRI) by recent small subcortical infarct, white matter hyperintensities (WMH), lacune, cerebral microbleed, enlarged perivascular space (ePVS) and brain atrophy. While pathology changes in the small vessels of brain tissue may be local manifestations of systemic small vessel injury, endothelial cell damage has been widely demonstrated to play an important role in this systemic pathological process. Thus, focusing on endothelial cell injury in CSVD would be crucial for a better understanding of CSVD.